Historic of therapeutic efficacy of albendazol sulphoxide administered in different routes, dosages and treatment schemes, against Taenia saginata in cattle experimentally infected - Zanetti Lopes, Welber Daniel [UNESP]; Cruz, Breno Cayeiro [UNESP]; Soares, Vando Edesio [UNESP]; Nunes, Jorge Luis N. [UNESP]; Pires Teixeira, Weslen Fabricio [UNESP]; Maciel, Willian Giquelin [UNESP]; Buzzulini, Carolina [UNESP]; Melo Pereira, Joao Carlos [UNESP]; Felippelli, Gustavo [UNESP]; Soccol, Vanette Thomaz; Oliveira, Gilson Pereira de [UNESP]; Costa, Alvimar Jose da [UNESP] (Elsevier B.V., 2014)
The present study aimed to notify the history of albendazole sulphoxide (ALB-SO) and albendazole (ALBZ) efficacy against Taenia saginata cysticercus (Cysticercus bovis) parasitizing experimentally infected bovines. A total of 11 efficacy trials were performed between the years of 2002 and 2010. In order to perform these trials, animals were individually inoculated with 2 x 104 eggs of T. saginata in each study's day zero (DO). For every trial, a positive control group (untreated infected animals) and a negative control group (animals that were neither infected nor treated) were used. ALB-SO or ALB were administered in the different dosages, in different days of treatments. In a last study with this formulation, this active principle was administered orally, mixed with the mineral supplement, on the 60th DPI, in a dosage of 30 mg/kg. In all trials, on the 100th DPI, all animals were euthanized and submitted to the sequenced slicing of 26 anatomical segments (fragments of approximately five millimeters) for the survey of T. saginata cysticercus. With the obtained results it is possible to verify that in the first trials, conducted in 2002, ALB-SO reached, independently of dosage and treatment scheme, efficacies superior to 98% (arithmetic means). The trials conducted in 2005 (2.5 mg/kg on the 30th, 60th, and 90th DPI) obtained values of efficacy all inferior to 60%. In 2008, the trials with 2.5 and 7.7 mg/kg demonstrated efficacy values inferior to 40%, for both dosages and treatment schemes (30th/60th/90th DPI and 60th DPI). When this formulation was administered orally on the dosage of 30 mg/kg on the 60th DPI, the efficacy against T. saginata cysticercus reached 88.28%. ALB administered orally showed efficacy values of 0.0%, 29.88% and 28.64% in the dosages of 5, 10 and 15 mg/kg, respectively, using the treatment schemes described above for each dosage. Based on the results of these trials, conducted in an eight year period (2002-2010) using the sequenced slicing method for evaluating the efficacy of the aforementioned formulations against T. saginata cysticercus, it is possible to observe that, amongst the few molecules used in the chemotherapic treatment against T. saginata larvae, ALB-SO, administered in varied routes, dosages and treatment schemes, the studies conducted in 2008, 2009, and 2010, have a low therapeutic efficacy against C bovis in Brazil, while ALBZ had insignificant efficacy values against T. saginata larvae parasitizing experimentally infected bovines. However, future studies using molecular biology will be necessary to assess whether the difference on the efficacy of the ALB-SO can be related to strain or another specific factor. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Bovine; Cysticercosis; Resistance; Strain; Treatment